2021
DOI: 10.3389/fonc.2021.657318
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Tumor-Associated Macrophages in Clear Cell Renal Cell Carcinoma: A Systematic Review and Meta-Analysis

Abstract: BackgroundTumor-associated macrophages (TAMs) are the major immune cells in tumor microenvironment. The prognostic significance of TAMs has been confirmed in various tumors. However, whether TAMs can be prognostic factors in clear cell renal cell carcinoma (ccRCC) is unclear. In this study, we aimed to clarify the prognostic value of TAMs in ccRCC.MethodsWe searched PubMed, Embase, and the Web of Science for relevant published studies before December 19, 2020. Evidence from enrolled studies were pooled and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 66 publications
(118 reference statements)
2
26
0
Order By: Relevance
“…We observed that M2 macrophages may enhance the proliferation, migration, invasion, and EMT of ccRCC through CXCL13 in our study. This is consistent with the finding M2 macrophage infiltration is a poor prognostic factor for RCC in the majority of studies [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…We observed that M2 macrophages may enhance the proliferation, migration, invasion, and EMT of ccRCC through CXCL13 in our study. This is consistent with the finding M2 macrophage infiltration is a poor prognostic factor for RCC in the majority of studies [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, TGF-β1 and Notch signaling may participate in DLK2-promoted ribosome biogenesis in ccRCC. Reportedly, M2 macrophage infiltration is a risk factor for poor prognosis in ccRCC patients, and M2 macrophage can serve as a potential biomarker for prognosis and novel targets for immunotherapy in ccRCC [26]. Moreover, both TGF-β1induced Snail signaling and the Jagged1-mediated Notch pathway can also promote the M2 polarization of the macrophage in the tumor microenvironment [61,62], and this means that DLK2-activated TGF-β1 and Notch signaling may participate in the M2 polarization of the macrophage in the ccRCC tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that ECM- [12,13], metabolism- [14][15][16], ribosome- [17], and immune-related genes [18][19][20][21] can serve as novel prognostic biomarkers for RCC. Moreover, the immune cell infiltration including T cells and macrophage also impacts disease prognosis in ccRCC [22][23][24][25][26]. These studied indicate that the genetic change in the tumor microenvironment can impact the survival outcome and disease prognosis in ccRCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Then we validated the expression of CD 163 (marker of TAMs) and TGF beta 1 (marker of CAFs) in PAAD tissues and adjacent normal tissues. TAMs, especially M2-like TAMs, as a major group of immune cells in TME, were reported playing critical roles in in tumorigenesis and progression process like tumor growth, metastasis, and treatment resistance ( 5 , 19 , 20 ). CAFs are the most essential components of the TME.…”
Section: Discussionmentioning
confidence: 99%